2011
DOI: 10.1162/jocn.2010.21431
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Brain Mechanisms Underlying the Conscious and Unconscious Control of Behavior

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 72 publications
6
84
0
Order By: Relevance
“…For instance, subliminal primes can influence prefrontal mechanisms of cognitive control involved in the selection of a task (11) or the inhibition of a motor response (12). Neural mechanisms of decision-making involve accumulating sensory evidence that affects the probability of the various choices until a threshold is attained.…”
Section: Unconscious Control and Decision-makingmentioning
confidence: 99%
“…For instance, subliminal primes can influence prefrontal mechanisms of cognitive control involved in the selection of a task (11) or the inhibition of a motor response (12). Neural mechanisms of decision-making involve accumulating sensory evidence that affects the probability of the various choices until a threshold is attained.…”
Section: Unconscious Control and Decision-makingmentioning
confidence: 99%
“…In general, larger (more negative) N2 components are observed following NoGo as compared to Go trials (Pfefferbaum et al, 1985), possibly reflecting effortful motor inhibition of the prepotent Go response (Bokura, Yamaguchi, & Kobayashi, 2001;Eimer, 1993;Falkenstein, Hoormann, & Hohnsbein, 1999;Lavric, Pizzagalli, & Forstmeier, 2004;Pfefferbaum et al, 1985;van Gaal et al, 2011).…”
Section: N2 Erp Componentmentioning
confidence: 99%
“…On these views, to consciously resist a prepotent action one should also be conscious of the urge to act, of the need to inhibit it, and subsequently of the volitional decision to do so. However, several studies have demonstrated nonconscious manipulation of motor-control processes via subliminal priming (e.g., van Gaal, Lamme, Fahrenfort, & Ridderinkhof, 2011;van Gaal, Ridderinkhof, van den Wildenberg, & Lamme, 2009). However, these studies focused on exogenously (stimuluselicited) inhibition, leaving open the question of whether there are nonconscious effects on volitional, endogenously generated intentional inhibition.…”
mentioning
confidence: 99%
“…Most studies using eventrelated potentials (ERPs) in the stop-signal and go/no-go task, have focused on the frontal N2 and P3, labeled the N2/P3 complex (e.g. Bekker et al, 2005a;Bokura et al, 2001;Eimer, 1993;Huster et al, 2010Huster et al, , 2011Kok et al, 2004;Ramautar et al, 2006a;Schmajuk et al, 2006;van Boxtel et al, 2001;van Gaal et al, 2011). Recent studies have found that the N2 is usually larger in unsuccessful than in successful stop trials suggesting a general role in response control, conflict monitoring and error processing (Dimoska et al, 2006;Enriquez-Geppert et al, 2010;Greenhouse and Wessel, 2013;Huster et al, 2013).…”
Section: Introductionmentioning
confidence: 99%